Child abuse and neglect – a review of risk assessment, care proceedings and ‘what works’ to address the issue - Turner, Sebrina (2020)
This thesis provides an investigation into Care Proceedings and potential treatment interventions to address the risk factors associated with child abuse and/or neglect. After an introduction to child abuse and neglect in chapter one, chapter two focuses on the first systematic review of a NICE recommended intervention, Multisystemic Therapy for Child Abuse and Neglect (MST CAN). This review highlights that there is emerging evidence that the intervention can reduce the risk of further child maltreatment by addressing risk factors identified at referral. However, there are limited high quality studies evidencing this and those that exist are predominantly from the USA.